Tax Incentives and Business Investment: Evidence from German Bonus Depreciation - Sebastian Eichfelder; Kerstin Schneider (Center for Economic Studies and ifo Institute (CESifo), 2014)
In this paper, we use an exogenous variation in tax regulations to analyze the impact of bonus depreciation programs on business investment. To promote economic convergence of Eastern and Western Germany after reunification, bonus depreciation tax incentives were granted for investments in Eastern Germany before 1999. Using business establishments in Western Germany as control group, we address the question if and to what extent these investment tax incentives boosted investment. In line with the theoretical literature, there is empirical evidence for strong and significant effects of the bonus depreciation program. The effects were stronger for long-lived capital goods, large businesses, and investments before the tax incentives were cut back in 1997. Moreover, there was a significant reduction in building investment in the year after the expiration of the program. This provides evidence for a shifting' of investment between periods with higher and lower benefits.
Keywords: G31; H25; H32; 330; business taxes; bonus depreciation; investment; tax incentive; investment tax incentive